Smoking cessation: an economic analysis and review of varenicline - Michele A Faulkner (Dove Medical Press, 2009)
Michele A FaulknerCreighton University School of Pharmacy and Health Professions, Omaha, NE, USAAbstract: Despite efforts to decrease tobacco use, smoking continues to be a leading cause of preventable morbidity and premature death. The associated economic burden is substantial, both in the form of direct costs (healthcare expenditures) and indirect costs (lost productivity), regardless of whether the burden is assessed from the standpoint of an employer, a health plan, or society as a whole. Cessation programs are considered among the most cost-effective in healthcare, and are often used as a benchmark for other medical interventions. This analysis specifically considers the cost-effectiveness of varenicline, a novel α4β2 partial agonist used for smoking cessation, in comparison to other approved therapies. Clinical trial data have demonstrated that varenicline has the ability to decrease cravings and withdrawal symptoms, and lessen positive reinforcement associated with smoking. Varenicline’s novel mechanism has translated into superior efficacy in comparison to other available therapies. For this reason, despite an initial cost that typically exceeds that of other medications, varenicline is a cost-effective option for smoking cessation.Keywords: cost-effectiveness, economic analysis, smoking cessation, varenicline